Sistem Rekrutmen Guru Agama Kontrak Pada Sekolah Dasar Negeri Di Kabupaten - Rosmi Rosmi (Jurusan Ilmu Administrasi Negara, 2019)
This study aims to describe the system of recruitment of contract religion teachers at the State Elementary School (SDN) in Bungo District. This research is a qualitative descriptive study. Research informants were selected through a purposive technique. The data used are primary and secondary data. Data collection through observation, documentation and interviews. Data is analyzed through interactive data analysis. The result showed that the recruitment of contract religious teachers at the State Elementary School (SDN) in Bungo District was carried out well and in accordance with applicable regulations. The recruitment system has several requirements and a recruitment process that must be followed. In addition, in the contract religion teacher recruitment system there are several procedures that must be followed by applicants. These procedures are: 1) application stage, 2) material selection, 3) written test, 4) interview, & 5) graduation announcement. Ther recruitment of contract religion teachers has been structured, the Bungo District Education and Culture Office has also made a predetermined budget for contract religion teachers in the State Elementary School (SDN).